Validation of the BIOCHIP test for the diagnosis of bullous pemphigoid, pemphigus vulgaris and pemphigus foliaceus. (30th July 2019) - Yang, A.; Xuan, R.; Melbourne, W.; Tran, K.; Murrell, D.F.
Abstract: Background: The BIOCHIP is a novel multiplex indirect immunofluorescence technique used in the serological diagnosis of bullous pemphigoid and pemphigus. The BIOCHIP method combines the screening of autoantibodies and target antigen‐specific substrates in a single miniature incubation field. Objective: To evaluate the diagnostic accuracy of the new immunofluorescence BIOCHIP multiplex tool in pemphigus and bullous pemphigoid. Methods: For the validation of the BIOCHIP, sera from patients with BP ( n  = 38), PF ( n  = 8) and pemphigus vulgaris (PV) ( n  = 23) were used. In addition, sera from disease control patients ( n  = 63) and healthy volunteers ( n  = 39) were used. The multiplex BIOCHIP and direct immunofluorescence (DIF) were performed for all BP, PF and PV patients. Additional indirect immunofluorescence (IIF) was performed on patients with BP, and ELISA was performed on patients with pemphigus. Results: The BIOCHIP mosaic showed a sensitivity of 86.8% and specificity of 85% for BP180 or BP230 being positive in BP. It demonstrated a sensitivity of 75% and specificity of 97.7% for Dsg1 in PF. The BIOCHIP was found to have a sensitivity of 60.9% and specificity of 73.6% for Dsg3 in PV. Conclusion: The BIOCHIP mosaic‐based immunofluorescence test is potentially a simple, time and effort saving test that can aid in the diagnosis and screening of BP, PV and PF. However, there is potential for interpretation bias and a learning curve that needs to be taken into consideration.